Culture, masculinities and violence against women - Kersten, Joachim (The British journal of criminology, 1996)
The visibility of male-dominated criminal violence differs substantially from culture to culture. Accordingly, a perception of masculinity and male dominated violence as monolithic categories is misleading. Australian, German, and Japanese data display significant variations in the visibility of violence against women. In the light of this, standard gender neutral explanations of comparative criminology will be reviewed. In a conceptualization of hegemonic masculinity' in the context of sexual assault the visibility of the rapist in Australia is interpreted as a consequence of economic and cultural crises of gender relations causing a transformation of hegemonic masculinity. At present, historical and political constellations in Germany and Japan result in the visibility of different features of male dominated violence